Do Saudi academic women use more feminised speech to describe their professional titles? An evidence from corpus - Reem Alkhammash; Haifa Al-Nofaie (Peoples' Friendship University of Russia (RUDN University), 2020)
The use of gendered occupational titles by women in higher-education settings has rarely been discussed either in the Saudi context or at the international level. This study investigates how Saudi women academics tend to represent themselves in their titles, in particular whether they use Arabic feminine or masculine markers. A corpus of 558,474 CVs was extracted from CVs published on Saudi women academics' websites at the two largest Saudi universities: King Saud University and King Abdulaziz University. The data gathered was analysed quantitatively. The frequencies of gender markers attached to positions' titles were analysed by adopting a corpus-based variationist linguistics. The findings reveal that the majority of Saudi women academics use more masculine markers in their academic titles than feminine gender markers. The study finds that both type of institution and the hierarchy of the academic discipline plays a significant role in the tendency to use masculine markers with the professional title, however, the academic discipline has no significant effect on the usage of masculine form. This study provides a cross-linguistic review of the use of gendered markers in other languages, such as French, German and Polish. It compares its findings with the findings of available international studies, a point that contributes to the significance of this study. It is hoped that this study will shed light on linguistic practices that should be reflective of policies that aim to empower Saudi women. This study contributes to a growing research of language and gender that focused on the linguistic representation of the titles of professional women and how grammar can be reflective of practices that are hindering women's empowerment in gender-specific languages.